Pemanfaatan Rebung Lokal dalam Inovasi Sambal Cabe Suhin (Toona Sureni) sebagai Upaya Peningkatan Pendapatan Petani di Kabupaten Kerinci: Pengabdian - Liona Efrina. S; Anggia Ayu Lestari; Elsya Fitrianisa; Ari Yopi Ispa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The use of local bamboo shoots in the innovation of Sambal Cabe Suhin product aims to increase the added value of agricultural products and farmers' income in Kerinci Regency. Bamboo shoots, as an abundant commodity in this region, have not been optimally utilized in the processed food industry. Through the traditional culinary innovation of Sambal Cabe Suhin combined with bamboo shoots, this product is expected to have higher competitiveness, longer shelf life, and wider market reach. This community service was carried out using descriptive methods and a participatory approach, involving farmer groups and MSMEs as the main partners. The results of the activity showed that the use of bamboo shoots in traditional chili sauce was able to increase farmers' income by 20-30% compared to the sale of fresh bamboo shoots. In addition, local wisdom-based processing also supports the preservation of culture and the potential for regional culinary tourism. The innovation of Sambal Cabe Suhin based on bamboo shoots is one of the creative strategies to strengthen the local economy and the welfare of the farming community.